2016
DOI: 10.1021/acs.jafc.5b04956
|View full text |Cite
|
Sign up to set email alerts
|

New Analytical Tool for the Detection of Ractopamine Abuse in Goat Skeletal Muscle by Potential Gene Expression Biomarkers

Abstract: In this study, quantification of mRNA gene expression was examined as biomarkers to detect ractopamaine abuse and ractopamaine residues in cashmere goats. It was focused on the identification of potential gene expression biomarkers and describing the coreletionship between gene expression and residue level by 58 animals for 49 days. The results showed that administration periods and residue levels significantly influenced mRNA expressions of the β2-adrenergic receptor (β2AR), the enzymes PRKACB, ADCY3, ATP1A3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Three replications per sample were used for the real-time PCR analysis, and the values are expressed as means ± the standard deviation. 37 ■ RESULTS AND DISCUSSION Effect of NO on Weight Loss, Flesh Firmness, and Softening Index. As shown in Figure 2, the wax apple weight loss rate increased gradually during storage and reached 3.45% in control fruit on day 12, but this increase was significantly reduced by NO treatment (P < 0.01).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Three replications per sample were used for the real-time PCR analysis, and the values are expressed as means ± the standard deviation. 37 ■ RESULTS AND DISCUSSION Effect of NO on Weight Loss, Flesh Firmness, and Softening Index. As shown in Figure 2, the wax apple weight loss rate increased gradually during storage and reached 3.45% in control fruit on day 12, but this increase was significantly reduced by NO treatment (P < 0.01).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Therefore, the results of 17 genes selected by a combination of targeted and non-targeted methods as biomarkers to identify animals treated with ractopamine were more satisfactory. This study revealed that the method established in the earlier literature [20] could be inhanced by adding eight genes selected by RNA-seq, which has a high throughput potential.…”
Section: Resultsmentioning
confidence: 91%
“…Compared with qRT-PCR, RNA-seq has higher detection throughput and a wider detection range, which provides a possibility of finding more biomarkers. To find more accurate biomarkers at the transcriptional level for β 2 -agonist drug misuse monitoring, this study improved the previous study [20] with a high-throughput RNA-seq technology. This approach is expected to further screen target genes to obtain more stable, sensitive and efficient biomarkers for higher detection precision.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations